Pengembangan Media Pembelajaran Macromedia Flash 8 Berbasis Pendekatan Konsep - Abdulloh Muwaffaq; Lilik Mawartiningsih (Universitas Sebelas Maret, 2018)
This study aims to develop learning media and know the feasibility of learning media Macromedia Flash 8basedapproach to the concept.This research is included in research and development (R & D) To develop Macromedia Flash 8 based learning media using ADDIE development model which includes five stages including Analysis (Analysis), Design (Design), Development (Development), Implementation (Implementation), evaluai (Evaluation). Product development using Macromedia Flash software. The subjects of the 2-person expert test and 2 person media experts, all test subjects are UNIROW lecturers, large-scale trials of 28 students of grade VIII Mts Hasyimiyah Bulu Bancar. Methods used in collecting data by collecting instruments in the form of assessment sheets for experts (expertjudgment), questionnaire (questionnaire) for students. This data quality is obtained in qualitative form then processed into quantitative data. Quantitative data is analyzed every aspect of the assessment. The final score obtained is converted to qualitative quality of the product by guidance according to the criteria of the ideal rating category.Thus the results of this development research shows that the development of learning media Macromedia Flash 8 based on the concept of students approach SMP / MTs class VIII meet the criteria of quality and worthy of use as a biological teaching materials.